Effects of Flipping STEM Classroom Learning Model Assisted by Live Worksheet on Students' Science Literacy on Concept of Heat Transfer Material - Dinda Aulia Oktaviana; Rahmat Firman Septiyanto; Asep Saefullah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Despite the importance of scientific literacy for learning, Indonesian students typically lack adequate literacy skills. The goal of this study is to determine whether teaching methods that use live worksheets and the flipping stem class paradigm can aid students in developing their scientific literacy. A quantitative quasi-experimental research design was used for this investigation. All pupils in class XI IPA 1–5 at a high school in Serang District made up the study's population. Class XI IPA 1 served as the experimental class for this study, and class XI IPA 2 served as the control class. Pretest, posttest, and student response questionnaires were the instruments used in this study. The posttest findings revealed that the experimental class outperformed the control class in terms of average score. This is demonstrated by utilizing the t-test to assess the outcome of the final test, where the values of t-count> t-table are 5.56>2.00. The control class's N-Gain scores 0.52 in the medium category and the experiment class 0.76 in the high category. According to the results of the student response survey, learning was put to good use in 87.1% of cases. According to the research, teaching with live worksheet while having the class turn around can enhance students' reading abilities, particularly in physics classes on heat transfer materials.